The Effects of Reversibility of H2-H3 Phase Transition on Ni-Rich Layered Oxide Cathode for High-Energy Lithium-Ion Batteries - Chen, Jie; Yang, Huiping; Li, Tianhao; Liu, Chaoyang; Tong, Hui; Chen, Jiaxin; Liu, Zengsheng; Xia, Lingfeng; Chen, Zhaoyong; Duan, Junfei; Li, Lingjun (Frontiers in Chemistry, 2019)
Although LiNi0.8Co0.1Mn0.1O2 is attracting increasing attention on account of its high specific capacity, the moderate cycle lifetime still hinders its large-scale commercialization applications. Herein, the Ti-doped LiNi0.8Co0.1Mn0.1O2 compounds are successfully synthesized. The Li(Ni0.8Co0.1Mn0.1)0.99Ti0.01O2 sample exhibits the best electrochemical performance. Under the voltage range of 2.7–4.3 V, it maintains a reversible capacity of 151.01 mAh·g−1 with the capacity retention of 83.98% after 200 cycles at 1 C. Electrochemical impedance spectroscopy (EIS) and differential capacity profiles during prolonged cycling demonstrate that the Ti doping could enhance both the abilities of electronic transition and Li ion diffusion. More importantly, Ti doping can also improve the reversibility of the H2-H3 phase transitions during charge-discharge cycles, thus improving the electrochemical performance of Ni-rich cathodes.